Analysis of the Implementation of E-Marketing Strategies in Micro, Small, and Medium Enterprises (MSMEs) in Medan City - Feby Aulia Safrin; Kartini Harahap (Citakonsultindo, 2025)
This study aims to analyze the implementation of e-marketing strategies by Micro, Small, and Medium Enterprises (MSMEs) in Medan, focusing on the food and beverage sector. The development of technology, particularly social media and other digital platforms, has provided opportunities for MSMEs to develop efficient and affordable marketing strategies. The research method employed in this study is descriptive qualitative, with primary data collected through in-depth interviews, focus group discussions (FGD), and direct observations, as well as secondary data obtained from the literature and official sources. The results show that the majority of MSME entrepreneurs in Medan have utilized social media platforms such as Facebook and Instagram, messaging applications such as WhatsApp, and online marketplaces such as Shopee to promote their products. The use of social media has proven to be effective in increasing product visibility at a lower cost than traditional marketing. However, some MSMEs are yet to optimize the use of marketplaces and food delivery applications because of the limited understanding of digital technology. The success of e-marketing implementation depends heavily on the technological readiness and capability of MSME entrepreneurs to leverage digital platforms. This study suggests the need to enhance digital literacy and provide technical training to MSME entrepreneurs to maximize the potential of digital marketing, thereby improving their competitiveness and marketing performance.